Gastro-intestinal Parasites of Assamese Macaque (Macaca assamensis Hodgson, 1840) in Shivapuri Nagarjun National Park, Kathmandu, Nepal - Pokhrel, Geeta; Maharjan, Mahendra (Journal of Institute of Science and Technology, 2015)
The macaque is a member of the sub family Cercopithecinae and family Cercopithecidae of primate order of mammalian class. Among five species of monkeys reported from Nepal, Assamese Macaque is one of the less common primate species. A total of 85 fresh faecal samples of Assamese Macaque (Macaca assamensis) were collected from Shivapuri Nagarjun National Park (SNNP), Kathmandu, Nepal. All the samples were macroscopically as well as microscopically examined to identify the distribution of gastrointestinal parasites using faecal floatation and Sedimentation techniques. The result revealed the distribution of three species of protozoan and seven species of helminthes parasite among Assamese Macaque of SNNP with the prevalence rate of 72.94% (62/85). Among protozoan parasites, Balantidium coli showed the highest prevalence (28.24%) followed by Entamoeba sp. (20%), and Isospora sp. (3.53%). Ascaris sp. was found to be distributed maximum (10.58%) among helminth parasites followed by Trichuris sp. (9.41%), Strongyloides sp. (8.24%), Moniezia sp. (8.24%), Oesophagostomum sp. (4.7%), Hookworm (4.7%) and Physeloptera sp.(1.17%). The present study highlights the necessity of considering parasitic diseases as one of the threat in conservation of Assamese Macaque. Journal of Institute of Science and Technology, 2014, 19(2): 53-57